The standing of the public interest - Etzioni, Amitai (Revista do Direito, 2016)
Liberal communitarianism holds that a good society is based on a carefully crafted balance between individual rights and the common good; that both normative elements have the same fundamental standing and neither a priori trumps the other. Societies can lose the good balance either by becoming excessively committed to the common good (e.g. national security) or to individual rights (e.g. privacy). Even societies that have established a careful balance often need to recalibrate it following changes in historical conditions (such as the 2001 attacks on the American homeland) and technological developments (such as the invention of smart cell phones).